UNIVERSITY AS A SCIENTIFIC AND SOCIAL INSTITUTE IN THE CONTEMPORARY RUSSIAN SOCIETY - Olga V. Zinevich; Elizaveta A. Ruzankina (Высшее образование в России)
The paper aims to illustrate a heuristic potential of an interpretation of the university as a scientific and social institute from the mode-2 science perspective. Thedemand of recontextualization of science and higher education leads to understanding of the transgressiveness of knowledge acquisition, and this means that the opposition between the scientific and social roles of the university may be overcomed. Taking into account that the most part of the contemporary Russian universities have never carried out a significant scientific function, the successfulness of the settlement of the opposition between thescientific and social roles of the university strictly depends on the role that the governmentmay play to provide an adequate grounds for the university to answer the demand of recontextualization.